Influence of non-genetic factors on body weights of Jakhrana kids - BHUSAN, SAKET; DASS, GOPAL (The Indian Journal of Animal Sciences, 2015)
Data on 789 Jakhrana kids born from 2007–2012 at the Institute were recorded to study the influence of various non-genetic factors on body weights of Jakhrana kids. The overall least squares means for body weights at birth, 3, 6, 9 and 12 months age were 2.77±0.06, 8.61±0.23, 12.33±0.26, 16.45±0.57 and 20.42±0.46 kg, respectively. Sex of kids, year of kidding and season of kidding had highly significant influence on all the body weights except significant effect of season on 6 month- body weights and nonsignificant influence on 9 month weights. The effect of parity and type of kidding was nonsignificant on all the body weights except highly significant effect of type of birth on birth weight, significant influence of parity on birth weight and significant effect on 3 month weight. Comparison of body weight means of kids indicated that male kids gained more weights than female kids, respectively, at birth, 3, 6, 9 and 12 month age. Kids born during second season (summer) showed significantly higher body weights at all ages except 3 month weight than those born during first season (winter). Year of kidding did not show any definite trend for kids body weights. Maximum growth of kids was recorded during 0–3 month (pre-weaning) age followed by 6–9, 9–12 and 3–6 age groups.